Assessment of nanomaterials in enhancing the thermophysical properties of phase change materials for thermal management - Arshad, Adeel (2021)
The rapidly growing and innovation of electronics devices with advanced smart and faster features raises a thermal challenge for an effective and clean cooling technology to ensure the reliable and safe operating temperature range of integrated circuits. A novel zero-noise, zero-power and zero-emission passive thermal management technology based on phase-change thermal energy storage systems has turned out a revolutionary advancement in smart cooling technologies. Such a cleaner, sustainable and reliable thermal management technology is integrated with such materials that have an intrinsic potential of absorbing/releasing the thermal energy during phase-transformation, called phase change materials (PCMs). The PCM can absorb/release the high energy storage density while the melting/solidification process with a stable phase-transition temperature range. Meanwhile, it has some issues mainly lower thermal conductivity, subcooling, less thermal stability, etc.